Islamic Religious Education Learning Strategies for Inclusion Students at Muhammadiyah High School - Anggraini, Fadhilla Nangroe; Mustofa, Triono Ali; Hadi, Abil Fida Muhammad Qois Al (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2024)
The issue of educational integration is a significant concern in meeting the special needs of regular school students, including Islamic Religious Education (PAI) subjects. Although the inclusive program aims to create an equitable learning environment, its implementation has various challenges, including limited teacher resources and lack of training. This study aimed to determine the PAI learning strategy for inclusive students at SMA Muhammadiyah 6 Surakarta and identify the obstacles faced during its implementation. This study used a qualitative method with a case study approach. Data was collected through direct observation of the learning process in grades 10-12, in-depth interviews with PAI teachers, students, and parents, and document analysis. The study results showed that inclusive learning strategies began with recognizing the unique needs of students, such as visual impairments, hearing impairments, hyperactivity, and intellectual disabilities. The strategies implemented included personalization of learning, use of audiovisual media, adaptation of teaching materials such as the Quran and Hadith, and collaboration with parents. Up to 40% of teachers felt adequately trained in inclusive learning, and revised assessments showed an increase in student engagement academically and socially by up to 30%. This study concludes that flexible, innovative, and inclusive learning strategies can enhance the academic and social potential of students with special needs. The implications of this study highlight the importance of intensive training for teachers, the development of more adaptive curricula, and educational policies that support inclusive learning in formal schools.